Lung Hypoplasia Without Other Congenital Anomaly- A Rarely Encountered Entity - Ghosh, Nilanjan; Das, Nabanita; Nayek, Kaustav (Journal of Nepal Paediatric Society, 2013)
A case of left sided lung hypoplasia is described in a seven year old female. She was admitted in our department with complaints of recurrent chest infections since infancy. Clinical examination revealed a febrile child with respiratory distress and with grossly diminished breath sound with patchy coarse crepitations on left hemithorax. X-ray chest revealed non homogenous opaque shadow on left hemithorax. Bronchscopy and CT thorax confirmed the diagnosis of left sided hypoplasia of lung. No other developmental anomaly was noted. DOI: http://dx.doi.org/10.3126/jnps.v33i2.7661 J Nepal Paediatr Soc. 2013; 33(2):138-140